"On Being Idolized" : construction d’une identité américaine à travers quelques poèmes de Robert Frost - Candice Lemaire (Anglophonia)
This article explores America’s literary canon through the major New England figure of farmer-poet Robert Frost (1874-1963), who offered a complex vision of American identity in his volumes, from that of the highly-acclaimed national artist to the uneasily translated and understood poet. Frost’s poetry, whose geographical limits are often blurred and which seems to constantly question and broaden its own Americanness, will also be analyzed here through its modern illustration in Jim Jarmusch’s movie Down by Law (1986).